Generation of long photonic nanojet by a self-assembled microdevice on optical fiber. (April 2023) - Yue, Ying; Hu, Xixi; Wang, Ruohui; Qiao, Xueguang
Abstract: Photonic nanojet (PNJ) is a narrowly focused and highly concentrated electromagnetic beam that is located on the shadow side of a transparent microdevice. Here we report nanoparticle self-assembled microdevices for PNJ generation. By the self-assembly technology, the microdevice has a controllable shape from a truncated sphere to a spherical segment. Its radius of curvature can be easily adjusted to ∼ 10 μ m by using the Plateau–Rayleigh unstable process. Its refractive index is ∼ 1.367 in 400 nm to 600 nm waveband. By integrating one of the self-assembled devices on the optical fiber facet, PNJ is generated with long decay length of 72 . 2 μ m and working distance of 79 . 8 μ m . In the experiment, the fiber-based PNJ exhibits a fluorescence enhancement factor of 9.65. Highlights: Nanoparticle self-assembly technology is first used to fabricate the microdevices for PNJ generation. Fiber-based PNJ probe is proposed to avoid the complex optical path alignment. A PNJ is constructed with a long decay length, narrow FWHM and far working distance. The fiber-based PNJ exhibits a fluorescence enhancement factor of 9.65.